Development of Mathematics Teaching Material Based on Lampungnese Ethomathematics - Endah Wulantina; Maskar, Sugama (Edumatica : Jurnal Pendidikan Matematika, 2019)
This research is a research development that aims to produce mathematics teaching materials based on Lampungnese etnomatematics. The research method consists of (1) data collection; (2) the design of teaching materials; (3) development of teaching materials; (4) validation I of teaching materials; (5) revision I of the validation results; (6) validation II; (7) revision II; (8) product trials; (9) final revision and production of teaching materials. Sampling was conducted on grade IV students at SDN 3 Kemiling Permai. The results of the validation of teaching materials from Lampung mathematicians and cultural experts gave an average score of 3.86 which was categorized as good or feasible, while the validation of teaching materials by the mathematics teacher gave an average score of 3.95 which was categorized as good or decent. In small class trials obtained an average score of student response questionnaire of 3.72 which is categorized as good or feasible. Then a large class trial obtained an average score of student response questionnaire of 3.89 which was categorized as good or feasible. The conclusion of this study is the lampungnese etnomatematics-based mathematics teaching materials are categorized as good and suitable for use in learning mathematics in elementary schools. Keynote: mathematical materials, lampungnese etnomatematics